Guest Editorial Special Section on PAR-CAD: Parallel CAD Algorithms and CAD for Parallel Architectures/Systems - Marculescu, Diana; Li, Peng (IEEE transactions on computer-aided design of integrated circuits and systems, 2012)
The five papers in this special section on PAR-CAD: Parallel CAD algorithms and CAD for parallel architectures/systems.